Effects of oxygen content and Pr substitution on vibrational anharmonicity of ErBa2Cu307.5 superconductors / Ahmad Kamal Yahya, Mohd Hanapiah Mohd Yusoff and Roslan Abd-Shukor - Yahya, Ahmad Kamal; Mohd Yusoff, Mohd Hanapiah; Abd-Shukor, Roslan (Faculty of Applied Sciences, 2004)
The temperature dependent ultrasonic longitudinal and shear velocities propagated at 10 MHz in superconducting (Er}.xPrx)Ba2Cu30 6.9 (x — 0.0, 0.1 and 0.2) and nonsuperconducting ErBa2CuiO6.j were used to evaluate effective Gruneisen parameters (yeff) for both modes. The elastic behavior of (Er1-xPrx)Ba2Cu306.9 (x = 0.0, 0.1 and 0.2) deviates from lattice anharmonicity theoretical curve generally above 160 K. Shear elastic response for less oxygen ErBa2Cu3O6.3 is described by purely anharmonic effects throughout the temperature range of 80 K -220 K. Deviation of elastic response for the longitudinal and shear modes from vibrational anharmonicity curves is oxygen-related and may be due to a phase transition involving oxygen ordering. The calculated effective Gruneisen parameters for (Er1-xPrx)Ba2Cu306.9 (x = 0.0, 0.1 and 0.2) for both longitudinal and shear modes were found to increase with Pr content, indicating increasing anharmonicity. The influence of Pr substitution on BCS electron-phonon coupling constant and its relationship to vibrational anharmonicity is discussed.